Arbuscular Mycorrhizal Symbiosis: Plant Friend or Foe in the Fight Against Viruses? - Miozzi, Laura; Vaira, Anna Maria; Catoni, Marco; Fiorilli, Valentina; Accotto, Gian Paolo; Lanfranco, Luisa (Frontiers in Microbiology, 2019)
Plant roots establish interactions with several beneficial soil microorganisms including arbuscular mycorrhizal fungi (AMF). In addition to promoting plant nutrition and growth, AMF colonization can prime systemic plant defense and enhance tolerance to a wide range of environmental stresses and below-ground pathogens. A protective effect of the AMF against above-ground pathogens has also been described in different plant species, but it seems to largely rely on the type of attacker. Viruses are obligate biotrophic pathogens able to infect a large number of plant species, causing massive losses in crop yield worldwide. Despite their economic importance, information on the effect of the AM symbiosis on viral infection is limited and not conclusive. However, several experimental evidences, obtained under controlled conditions, show that AMF colonization may enhance viral infection, affecting susceptibility, symptomatology and viral replication, possibly related to the improved nutritional status and to the delayed induction of pathogenesis-related proteins in the mycorrhizal plants. In this review, we give an overview of the impact of the AMF colonization on plant infection by pathogenic viruses and summarize the current knowledge of the underlying mechanisms. For the cases where AMF colonization increases the susceptibility of plants to viruses, the term “mycorrhiza-induced susceptibility” (MIS) is proposed.